Analisis Karakteristik Fluida dan Estimasi Temperatur Reservoir Desa Sawangan Kabupaten Minahasa Utara - Gloria Permatasari; Armstrong F. Sompotan; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2024)
Geothermal energy is the heat stored within the Earth’s subsurface rocks and the fluids contained within them. Indonesia, located on the Ring of Fire, has significant geothermal potential, particularly in North Sulawesi. This study aims to assess the geothermal energy potential in Sawangan Village, North Minahasa Regency, specifically at the Kepangian River hot springs. The research was conducted by analyzing the fluid characteristics and estimating the geothermal reservoir temperature using geochemical fluid analysis and geothermometer calculations. The analysis Involved laboratory testing of fluid samples, followed by data processing using Na-K and silica geothermometers, and plotting on a Na-K-Mg ternary diagram. The results indicate that the fluid type at the Kepangian River hot springs is immature water, with an estimated reservoir temperature ranging from 240.04°C to 267.01°C, which classifies it as a high-temperature reservoir.